Strategic Tourism Development by the Municipal Government of Baucau, Timor-Leste - Ximenes, Rui; Utari Dewi, Nyoman Diah; Widnyani, Ida Ayu Putu Sri (Penerbit Goodwood, 2024)
Purpose: This study examines the strategic development of tourism undertaken by the Local Government of Baucau Municipality, Timor Leste, with a focus on infrastructure, promotion, destination management, and human resource development. Research methodology: This study uses qualitative methods to collect data through in-depth interviews with local government representatives, tourism industry stakeholders, local communities, and other relevant parties. Additionally, direct observations and document analysis were conducted to gain a comprehensive understanding of the tourism development strategies in the region. Results: The study reveals that the Local Government of Baucau Municipality has implemented several strategies for tourism development. Promotion plays a key role, with the local government using both conventional and social media platforms to enhance the visibility of Baucau’s tourist destinations. Furthermore, human resource development is prioritized with the government providing training and education to improve the quality of service in areas such as customer service, destination management, and tourism business management. This study also highlights the impact of central government budget allocations to the Tourism Department in Baucau, which supports these initiatives. Limitations: The research is limited by the scope of available data, particularly regarding the full impact of tourism initiatives and budget allocations, which may evolve over time. Contribution: This study provides valuable insights into the strategic planning of tourism in Baucau Municipality, emphasizing the importance of a context-specific, comprehensive approach to tourism development. This serves as a reference for future efforts to improve tourism infrastructure, promotion, and human resource management in the region.